PENGARUH PENAMBAHAN LIMBAH GRANIT TERHADAP KUAT TEKAN BETON - HADI, SURYA (GANEC SWARA, 2020)
Concrete is a mixture consisting of cement, sand, gravel, and water. To get good quality in the process it is necessary to add additional materials (admixture or additive), waste, or other materials with a certain comparison value. In this case, the use of granite and natural stone waste as a material for making concrete is quite potential because the waste of granite and natural stone as a material for making concrete is easy to find. In this study, a destructive method testing is used make concrete. This study aims to determine the compressive strength of concrete by utilizing waste granite and natural stone as a material for making concrete. In this study 12 (twelve) cylindrical specimens are used with a diameter of 150 mm and a height of 300 mm, with a percentage increase in granite waste of 0%, 8%, 10% and 12%. The test is carried out after 28 days of concrete in accordance with ASTM C496-90, then the cylindrical test specimens are tested with a compressive load using a CTM (Compression Testing Mechine). The planned compressive strength is 25 MPa. From the results of the study, the normal compressive strength of 26.09 MPa is obtained. On the addition of granite waste with a percentage of 8%, 10% and 12%, the compressive strength is obtained at 24.58 MPa, 22.69 MPa and 21.28 MPa respectively. Addition of granite waste to normal concrete actually reduces the compressive strength of concrete. The higher the percentage of additional granite waste, the weaker compressive strength of concrete becomes. In this study it is concluded that the compressive strengthof normal concrete is higher than that of concrete with the addition of granite waste